Chapter Paesaggio, antropologia e storia: eco-memoria, condizione preliminare dei processi di riterritorializzazione - Tarpino, Antonella (Territori, 2023)
Eco-memory looks back at the territory along space and time, in the story of how natural systems co-evolve with human settlements in a critical intersection, each time rethought, among man, nature and territories; in order to give visibility and prospects to the many fragile, invisible landscapes that fell off the development axis along the ungoverned industrialisation of the last century. On the one hand, it crosses historiography in a declination of temporal measurement (from the long to the short and very short term) that cannot be subsumed under today's temporal acceleration, wiping out the past to the point of making territories we live in unrecognisable to our very eyes. On the other, it refers to an anthropology focusing on the spatial dimension and aimed at proposing a revolution of the gaze so as to reread eco-territorial dynamics no longer from the centre (cluttered by the rubble of a systemic crisis) but from the margins, to express new modes of neo-communitarian self-government.